FACTORS RELATED TO TWO-WHEELED SAFETY RIDING BEHAVIOR AT PRODUCTION PLANNING WORKERS AT PT. YUASA BATTERY INDONESIA IN 2021 - Irawan, Siti Rachmawati Khoirunnadhira; Putri, Eka Cempaka; Situngkir, Decy; Yusvita, Fierdania; Rusdy, Mirta Dwi Rahmah (Faculty of Vocational Studies, Universitas Airlangga, 2022)
Background: The high number of uses of this means of transportation has hidden dangers for its use. Based on data from the Police Traffic Corps, it was discovered that the number of accidents involving motorcycles in 2020 reached 107.500 cases. Purpose: To determine the factors related to the safety behavior of two-wheeled driving (safety riding) on workers in the production planning division at PT. Yuasa Battery Indonesia in 2021. Method: It is a quantitative study with a cross-sectional study design. The population of this study were 76 workers in the production planning division at PT. Yuasa Battery Indonesia. The sample used in this study amounted to 50 workers derived by random sampling technique. Data collection used primary and secondary data obtained from questionnaires and companies regarding the number and causes of traffic accidents that occurred to workers as well as records related to the implementation of safety riding training. Result: 28 workers (56%) in the production planning section behaved unsafety riding. The results of the chi-square test showed that there was a relationship between age (p-value=0.002), knowledge (p-value=0.000), attitude (p-value=0.000), driving skills (p-value=0.000) and safety driving behavior (safety riding), and there is no relationship between education (p-value=1.000) with safety riding. Conclusion: There was a relationship among the variables of age, safety riding knowledge, driving attitude, and driving skills, meanwhile there was no relationship between education variable and two-wheel driving safety behavior.